Cerebral metabolism is not affected by moderate hyperventilation in patients with traumatic brain injury - Brandi, Giovanna (Crit Care, 2019)
BACKGROUND: Hyperventilation-induced hypocapnia (HV) reduces elevated intracranial pressure (ICP), a dangerous and potentially fatal complication of traumatic brain injury (TBI). HV decreases the arteriolar diameter of intracranial vessels, raising the risk of cerebral ischemia. The aim of this study was to characterize the effects of moderate short-term HV in patients with severe TBI by using concomitant monitoring of cerebral metabolism, brain tissue oxygen tension (PbrO(2)), and cerebral hemodynamics with transcranial color-coded duplex sonography (TCCD). METHODS: This prospective trial was conducted between May 2014 and May 2017 in the surgical intensive care unit (ICU) at the University Hospital of Zurich. Patients with nonpenetrating TBI older than 18 years of age with a Glasgow Coma Scale (GCS) score < 9 at presentation and with ICP monitoring, PbrO(2), and/or microdialysis (MD) probes during ICU admission within 36 h after injury were included in our study. Data collection and TCCD measurements were performed at baseline (A), at the beginning of moderate HV (C), after 50 min of moderate HV (D), and after return to baseline (E). Moderate HV was defined as arterial partial pressure of carbon dioxide 4–4.7 kPa. Repeated measures analysis of variance was used to compare variables at the different time points, followed by post hoc analysis with Bonferroni adjustment as appropriate. RESULTS: Eleven patients (64% males, mean age 36 ± 14 years) with an initial median GCS score of 7 (IQR 3–8) were enrolled. During HV, ICP and mean flow velocity (CBFV) in the middle cerebral artery decreased significantly. Glucose, lactate, and pyruvate in the brain extracellular fluid did not change significantly, whereas PbrO(2) showed a statistically significant reduction but remained within the normal range. CONCLUSION: Moderate short-term hyperventilation has a potent effect on the cerebral blood flow, as shown by TCCD, with a concomitant ICP reduction. Under the specific conditions of this study, this degree of hyperventilation did not induce pathological alterations of brain metabolites and oxygenation. TRIAL REGISTRATION: NCT03822026. Registered on 30 January 2019.